Meningkatkan Kesiapan Siswa TK Yaa Bunayya Lodoyo Untuk Menerapkan “New Normal Life” Pada Pandemi Covid 19 - Anita Rahmawati; Yeni Kartika Sari; Ning Arti Wulandari (UNUSA Press, 2020)
The covid-19 pandemic that occurred in the world, including Indonesia, encouraged the government to urge people to adopt new normal habits as a measure to prevent the transmission of covid 19. The community, especially parents and students of Yaa Bunayya Lodoyo Kindergarten, still do not have optimal knowledge and behavior to prevent Covid-19 transmission. This community service aims to improve the readiness of TK Yaa Bunayya Lodoyo students to implement